The Business of Software: Estimation Is Not Evil. - Armour, Phillip G. (Communications of the ACM, 2014)
The article provides insights on reconciling agile approaches and project estimates in software development. In the so-called waterfall life cycle approach, only a few projects could or did legitimately predefine 100% of their requirements and design prior to development. The cost of the project and the cost of risk are both estimates and uncertain, but are said to be essential to making good business decisions. Agile projects should have a target end state where they can work, with estimation as one of the business management elements.